(untitled) (BIRDEM Medical Journal, 2021)
Melioidosis is an emerging infectious disease in Bangladesh. Reported cases are mostly diagnosed among inhabitants of central and north-east zone of the country. We report three cases of melioidosis occurring among patients with diabetes mellitus and chronic kidney disease from not well-known endemic areas within the country. Patients presented with fever, anorexia and weight loss. Laboratory reports confirmed growth of Burkholderia pseudomallei from blood and urine. These cases are reported to increase awareness among physicians regarding melioidosis occurring beyond the so-called hot spots in Bangladesh. BIRDEM Med J 2021; 11(3): 239-242